Kill the messenger [videorecording (DVD)] - Renner, Jeremy; DeWitt, Rosemarie; Liotta, Ray; Nelson, Tim Blake; Webb, Gary, 1955-2004; Schou, Nick ([Publisher not identified], 2015)
Webb stumbles onto a story which leads to the shady origins of the men who started the crack epidemic on the nation's streets, and further alleges that the CIA was aware of major dealers who were smuggling cocaine into the U.S., and using the profits to arm rebels fighting in Nicaragua. Despite warnings from drug kingpins and CIA operatives to stop his investigation, Webb keeps digging to uncover a conspiracy with explosive implications.